Contested national and digital space, the Orthodox Church, and the new forms of religious engagement: comparative insights from Georgia and Greece - Margvelashvili, Kristine (Frontiers in Political Science, 2025)
As political actors, Orthodox Churches (OCs) attempt to define national identity and promote religious nationalism. This paper explores new forms of religious engagement in Greek and Georgian Orthodoxy, with a focus on the use of social media. In both countries, the church employs cultural capital to advance its discursive struggle for national identity while utilizes its veto power. These online discursive dynamics are more intense in Georgia, where the church’s political influence is greater. In Greece, the church is more cautious and limits its authority online to religious matters, avoiding high-stakes political debates. The interplay between national identity, religion, and digital space continues to shape political landscapes in Orthodox societies, with church-driven nationalism remaining a potent force.